Report of the Jumpstarting Brain Tumor Drug Development Coalition and FDA clinical trials neuroimaging endpoint workshop (January 30, 2014, Bethesda MD) - Wen, Patrick Y.; Cloughesy, Timothy F.; Ellingson, Benjamin M.; Reardon, David A.; Fine, Howard A.; Abrey, Lauren; Ballman, Karla; Bendszus, Martin; Buckner, Jan; Chang, Susan M.; Prados, Michael D.; Pope, Whitney B.; et al. (Neuro-Oncology, 2014)
Abstract. On January 30, 2014, a workshop was held on neuroimaging endpoints in high-grade glioma. This workshop was sponsored by the Jumpstarting Brain Tumor
Gesehen am 16.07.2020